2013
DOI: 10.1111/pbi.12107
|View full text |Cite
|
Sign up to set email alerts
|

Trait stacking via targeted genome editing

Abstract: SummaryModern agriculture demands crops carrying multiple traits. The current paradigm of randomly integrating and sorting independently segregating transgenes creates severe downstream breeding challenges. A versatile, generally applicable solution is hereby provided: the combination of high-efficiency targeted genome editing driven by engineered zinc finger nucleases (ZFNs) with modular 'trait landing pads' (TLPs) that allow 'mix-and-match', on-demand transgene integration and trait stacking in crop plants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
126
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(137 citation statements)
references
References 42 publications
1
126
0
4
Order By: Relevance
“…Thus, it is possible to perform specific modifications to a DNA sequence, such as gene insertions, replacements or deletions [including transgenes; Chen and Gao (2013), Rinaldo and Ayliffe (2015)]. Moreover, when using TALENs or CRISPR/Cas9, it is possible to perform gene stacking to introduce multiple genes in one locus; this increases the stability and facilitates inheritance of thus obtained traits (Ainley et al, 2013;D'Halluin et al, 2013). If using multiple nucleases at once, it is also possible to perform large DNA deletions (allowing removal of entire gene regulatory networks), inversions, or translocations (Chen and Gao, 2013).…”
Section: Applications Of Site-directed Nucleasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is possible to perform specific modifications to a DNA sequence, such as gene insertions, replacements or deletions [including transgenes; Chen and Gao (2013), Rinaldo and Ayliffe (2015)]. Moreover, when using TALENs or CRISPR/Cas9, it is possible to perform gene stacking to introduce multiple genes in one locus; this increases the stability and facilitates inheritance of thus obtained traits (Ainley et al, 2013;D'Halluin et al, 2013). If using multiple nucleases at once, it is also possible to perform large DNA deletions (allowing removal of entire gene regulatory networks), inversions, or translocations (Chen and Gao, 2013).…”
Section: Applications Of Site-directed Nucleasesmentioning
confidence: 99%
“…The whole stack of the four transgenes was inherited in the subsequent generations as a single genetic unit and field experiments confirmed that all of the genes were expressed. Ainley et al (2013) introduced pat and aad1 genes that confer resistance to glufosinate and aryloxyphenoxypropionate herbicides, respectively, in maize. The gene knock-in was performed in two steps using ZFNs.…”
Section: " 46mentioning
confidence: 99%
“…In order to be competitive with nuclease mediated gene insertion in plants, 24,25 at least 2-5% of the embryogenic transgenic events should display the targeted insertion mediated by the piggyBac fusion transposase. The advantage to using piggyBac fusion transposase over a nuclease for gene insertion is that the transgenic plant would not need to be sequenced for unintended genetic changes that could occur with nucleases.…”
Section: Abstract Chimeric Transposase; Insect Transposon; Plants; Simentioning
confidence: 99%
“…Because the IPK1-gene is disrupted by a transgenic phosphinotricin acetyltransferase gene sequence insert (which mediates tolerance to the herbicide agent phosphinotricin (glufosinate) and is used for selection of HDR integration events), the maize plants with a reduced phytate trait still contain foreign sequences in the end product. HDR-mediated gene integration has also been used for sequential stacking genes into a so-called 'safe harbour' locus, which is a chromosomal location where genes can integrate and function in a predictable manner (Ainley et al 2013). An advantage of gene stacking at a single locus is that during subsequent crossings the stacked transgenes segregate as a single locus, which would simplify breeding of plant lines with stacked transgenes (Nandy et al 2015;Srivastava and Thomson 2016).…”
Section: Application Areasmentioning
confidence: 99%